The Effect of Singapore Interest Rates on the Joint Stock Price Index (JCI) in the Banking Sector - Cahya M, Intan; Prasetyo, Tri Joko; Evana, Einde; Amelia, Yunia (Green Publisher Indonesia, 2022)
This research aims to examine the influence to determine the effect of Singapore interest rates on the Jakarta Composite Index (JCI) in the banking sector. This research is a quantitative research. The data were collected using documentation. In order to achieve the goal study, this study was conducted by using the type of proportional sampling method so that as many as 36 banking samples were obtained.The result showed that the Singapore interest rate (SIBOR) had a significant positive effect on the Composite Stock Price Index (CSPI) of the banking sector, this was indicated by the value of sig. on the SIBOR variable of 0.008 <0.05 and has a beta value of -26.527. And has a t-count value of -2.819 < from t-table which is 2.719.